Hungarian Monitoring, 24 November 1988 . [Magyar rádiófigyelő], 1988. november 24 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Rakowski's visit to Austria - Romanian response to the Hungarian expulsion order - Pogrom in Azerbaijan Domestic Affairs: - Romanian ambassador to Hungary deported today: he has 72 hours to leave the country - Hungary recognizes formation of independent Palestinian state: deputy foreign minister Dr Gábor Nagy - A first in the history of Hungarian Radio: live broadcast from parliament during parliamentary sitting - "I didn't sum up my activities", Károly Grósz relieved of office at his own request with 28 votes against and 13 abstentions - Parliament nominates Miklós Németh as Ministerial Council president; Rezső Nyers becomes minister of state - President of national Planning Office reports on government's stability program, results after one year and expected economic-financial outlook - Second day of university students' demonstrations Külpolitika: - Rakowski ausztriai látogatása - A román válasz a magyar kiutasító határozatra - Azerbajdzsánban pogrom volt Belpolitika: - Ma kiutasították Románia magyarországi nagykövetét, akinek 72 órán belül el kell hagynia az országot - Magyarország elismeri a független palesztin állam kikiáltását, - Közölte dr. Nagy Gábor külügyminiszter-helyettes - A Magyar Rádió történetében először: élő közvetítés a parlamentből, országgyűlési ülésszak - "Mérleget nem készítettem" - Mondta a leköszönő miniszterelnök, Grósz Károly, akit 28 ellenszavazattal, 13 tartózkodás mellett - Saját kérésére - Felmentettek tisztségéből - Az Országgyűlés Németh Miklóst választotta a Minisztertanács elnökének. Nyers Rezső államminiszter lett - Az országos Tervhivatal elnökének beszámolója a kormány stabilizációs programjáról, az egy éves tapasztalatokról és a várható gazdasági-pénzügyi kilátásokról - A diákdemonstráció második napja